2020
DOI: 10.1186/s13287-020-02056-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells promote osteogenic differentiation in co-cultured with mesenchymal stem cells via the MAPK-dependent pathway

Abstract: Background The role of bone tissue engineering is to regenerate tissue using biomaterials and stem cell-based approaches. Combination of two or more cell types is one of the strategies to promote bone formation. Endothelial progenitor cells (EPCs) may enhance the osteogenic properties of mesenchymal stem cells (MSCs) and promote bone healing; this study aimed to investigate the possible mechanisms of EPCs on promoting osteogenic differentiation of MSCs. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 69 publications
(68 reference statements)
1
21
0
1
Order By: Relevance
“…Previous results showed that the interaction of ECs and stem cells promotes osteogenic differentiation and vascularized bone regeneration and also enhances angiogenic factor expression [ 46 – 48 ]. Moreover, blood vessel growth is associated with bone formation, especially the specialized type H vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that the interaction of ECs and stem cells promotes osteogenic differentiation and vascularized bone regeneration and also enhances angiogenic factor expression [ 46 – 48 ]. Moreover, blood vessel growth is associated with bone formation, especially the specialized type H vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK signaling in human bone marrow-derived MSCs promotes osteogenic differentiation [ 64 , 65 ], while upregulation of ERK/p-ERK pathway contributes to the suppression of osteogenesis of MSCs [ 27 , 44 , 46 ]. ERK/p-ERK may regulate other pathways, such as PI3-kinase/Akt or P38 pathway, to affect osteogenic differentiation of hMSC-DP [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that apart from Wnt/β-catenin pathway, there were several canonical pathways related to the osteogenic and adipogenic differentiation of MSCs, such as Akt, MAPK and Hedgehog pathway 27 29 . To further clarify whether these pathways play a role in the abnormal differentiation of active cGVHD-MSC, we then assayed the expression of proteins regulated by these pathways, Including Akt, p38 MARK and Sonic Hedgehog (SHH).…”
Section: Resultsmentioning
confidence: 99%